Republic of Texas railroad stock certificate, - Perry, James Franklin, 1790-1853; Fisher, George, 1795-1873 ([Brazos and Galveston Rail Road Company], 1839)
Stock certificate "No. 36" partly printed and partly filled in with ms. ink. acknowleding the payment by George Fisher for shares of stock of the Brazos and Galveston Rail Road Company. Signed as witnesses by Wm. J. Bryan and Geo. L. Hammeken on March 18th 1839.